THE ROLE AND IMPORTANCE OF MORAL VALUES IN SOCIETY - Mo’ydinov Hamidullo Raxmatillo o’g’li (American Journals Publishing, 2024)
In this article, moral values have a continuous history in world culture and history, and are based on the national punishment, men, and thinking of the Uzbek people.
Keywords: Ethics, human rights and freedom, Ethical Social Services.